Incorporating Intellectual Property Rights and E-Commerce: Supply Chain Strategy to Strengthen the Competitiveness of SMEs - Retnaningdiah, Dian; Resmi, Siti; Kurniawati, Indah; Suhendra Winarso, Beni (International Journal of Supply Chain Management, 2020)
Abstract- This research aims to analyze the use of e-commerce and Intellectual Property Rights (IPR), especially the supply chain strategy for Small Business Enterprises (SMEs) as an effort to strengthen business competitiveness. This study uses an experimental design by providing intervention to respondents. Descriptive analysis was carried out to reflect the data obtained from the process of identifying the profiles of several SMEs and this study involved 40 SMEs in Yogyakarta. The data was processed using inductive analysis with paired sample t-test to find out the difference between e-commerce insights and IPR ownership before and after the experiment. One-Sample Kolmogorov Smirnoff is used to test data normality to determine different types of tests. The findings demonstrate that there are significant differences before conducting the experiment and after. The research shows that communication is a key tool ensuring the efficiency of supply chain cooperation as perceived seriously by the SME. The experiment indicates the significant level of 0.003 is lower than alpha of 0.05 for e-commerce. While the ownership of IPR such as trademarks showed significant gains as well, as indicated by the significant level 0.000 lower than alpha 0.05. The result of experimental method has made marketing techniques with e-commerce and IPR ownership.